Transcriptomic Analysis of Mecp2 Mutant Mice Reveals Differentially Expressed Genes and Altered Mechanisms in Both Blood and Brain - Sanfeliu, Albert; Hokamp, Karsten; Gill, Michael; Tropea, Daniela (Frontiers in Psychiatry, 2019)
Rett Syndrome is a rare neuropsychiatric disorder with a wide symptomatology including impaired communication and movement, cardio-respiratory abnormalities, and seizures. The clinical presentation is typically associated to mutations in the gene coding for the Methyl CpG Binding Protein 2 (MECP2), which is a transcription factor. The gene is ubiquitously present in all the cells of the organism with a peak of expression in neurons. For this reason, most of the studies in Rett models have been performed in brain. However, some of the symptoms of Rett are linked to the peripheral expression of MECP2, suggesting that the effects of the mutations affect gene expression levels in tissues other than the brain. We used RNA Sequencing in Mecp2 mutant mice and matched controls, to identify common genes and pathways differentially regulated across different tissues. We performed our study in brain and peripheral blood, and we identified differentially expressed genes (DEGs) and pathways in each tissue. Then, we compared the genes and mechanisms identified in each preparation. We found that some genes and molecular pathways which are differentially expressed in brain are also differentially expressed in blood of Mecp2 mutant mice at a symptomatic – but not pre-symptomatic- stage. This is the case for the gene Ube2v1, linked to ubiquitination system, and Serpin1, involved in complement and coagulation cascades. Analysis of biological functions in the brain show the enrichment of mechanisms correlated to circadian rhythms, while in the blood are enriched the mechanisms of response to stimulus -including immune response. Some mechanisms are enriched in both preparations, such as lipid metabolism and response to stress. These results suggest that analysis of peripheral blood can reveal ubiquitous altered molecular mechanisms of Rett and have applications in diagnosis and treatments’ assessments.